COVID-19 and cardiovascular complications: updates of emergency medicine - Jianli Zhao; Yaoli Xie; Zhijun Meng; Caihong Liu; Yalin Wu; Fujie Zhao; Xinliang Ma; Theodore A. Christopher; Bernard J. Lopez; Yajing Wang (Emergency and Critical Care Medicine)
Abstract. Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and SARS-CoV-2 variants, has become a global pandemic resulting in significant morbidity and mortality. Severe cases of COVID-19 are characterized by hypoxemia, hyperinflammation, cytokine storm in lung. Clinical studies have reported an association between COVID-19 and cardiovascular disease (CVD). Patients with CVD tend to develop severe symptoms and mortality if contracted COVID-19 with further elevations of cardiac injury biomarkers. Furthermore, COVID-19 itself can induce and promoted CVD development, including myocarditis, arrhythmia, acute coronary syndrome, cardiogenic shock, and venous thromboembolism. Although the direct etiology of SARS-CoV-2–induced cardiac injury remains unknown and underinvestigated, it is suspected that it is related to myocarditis, cytokine-mediated injury, microvascular injury, and stress-related cardiomyopathy. Despite vaccinations having provided the most effective approach to reducing mortality overall, an adapted treatment paradigm and regular monitoring of cardiac injury biomarkers is critical for improving outcomes in vulnerable populations at risk for severe COVID-19. In this review, we focus on the latest progress in clinic and research on the cardiovascular complications of COVID-19 and provide a perspective of treating cardiac complications deriving from COVID-19 in emergency medicine.